2022
DOI: 10.1088/1361-6455/ac9cae
|View full text |Cite
|
Sign up to set email alerts
|

Study of bound and resonant states of NS molecule in the R-matrix approach

Abstract: The bound and resonance states along with corresponding autoionization widths for nitrogen sulphide (NS) molecule are determined using electron NS$^+$ cation scattering calculations. The calculations are performed for $^2\Sigma^+$, $^2\Pi$ and $^2\Delta$ total symmetries using the {\em ab initio} R-matrix method for both bound and continuum states. Calculations are performed on a grid of 106 points for internuclear separations between 1.32 and 3 \AA. The resonance states yield dissociative potential curves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The present nuclear dynamics study relies on the molecular data sets recently calculated in the framework of the Rmatrix theory [17]. We have found five molecular states of the cation, and for the ionization channels, the partial waves we took into account for the incident electron are s, p, and d for the 2 Σ + states and p and d for the 2 Π ones [17].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The present nuclear dynamics study relies on the molecular data sets recently calculated in the framework of the Rmatrix theory [17]. We have found five molecular states of the cation, and for the ionization channels, the partial waves we took into account for the incident electron are s, p, and d for the 2 Σ + states and p and d for the 2 Π ones [17].…”
Section: Resultsmentioning
confidence: 99%
“…A summary of the relevant PECs, taken from Iacob et al [17], can be seen in figure 1. The black curve stands for the Energy diagram of the NS + /NS molecular system, relevant for dissociative recombination, compiled from [17].…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moving from the cold gas approximation to the state-to-state approach, the A&M community has demonstrated a growing maturity in developing processes for curating dynamical data pertinent to the kinetic modeling of low temperature plasmas (LTPs), with the goal of furthering the understanding of fundamental processes involving both electron and heavy species collisions. [86][87][88][89][90][91][92][93][94] It has recently been shown that research in the food industry and technology suggest the potential usage of plasmas in the treatment of plants such that they may be treated without pesticides or other toxic agents. 95,96 Accordingly A&M datasets of interest for the bio/chemistry and food industry, which include electrons and ions collisions with small molecules and various excited species, are being made available.…”
Section: Acol-database For Collisional Processesmentioning
confidence: 99%